PERAN ISLAMIC HUMAN RIGHTS COMMISSION (IHRC) DALAM ADVOKASI ISLAM PADA MASYARAKAT PRANCIS - Huwaida, Salwa Shabrina; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
France is a country that upholds the principles of liberté, égalité, fraternité. This principle supports the emergence of the concept of laïcité or commonly referred to as secularism. Laïcité made France have many records of religious discrimination, including Islam. The Islamic Human Rights Commission (IHRC) is attempting to advocate Islamic narratives to deal with this Islamophobia with the Counter Islamophobia Kit project. Authors use qualitative research methods, with data collection techniques through library studies derived from journals, books, websites, and articles. This study used the Transnational Advocacy Network theory to assess how the IHRC played the role of Islamic advocacy in French society. The findings of this study show that the IHRC contributed to Islamic advocacy to French society by conducting four Transnational Advocacy Network tactics: symbolic politics by attempting to change the view of the veil considered restrictive, information politics by gathering information about Islam in France, and information about it. In the United States, the European Parliament cooperates with other local institutions by inviting other local institutions to participate, and accoutability politics by bringing the European Parliament to work together, but there are still challenges and obstacles to reducing the problem of Islamophobia. Keywords: Laïcité, IHRC, Islamophobia, Advocacy.